Projeto Quilombo do Barranco: a preservação indenitária através da arquitetura - Pinheiro, Manuella de Mendonça Menezes (Brasil, 2022)
This Final Project aims to study and develop the “Project Quilombo do Barranco, the identity preservation through architecture.” The current work includes a design proposal whose purpose is to preserve the ancestral identity of the quilombolas, using their culture, traditions and their historic legacy as the main architectural concept. The quilombolas have cultural features on their territoriality, affirmed by religious practices and by their daily routine in the community. They resist against discriminatory acts, social invisibility and the city urban expasion through the years. The archicteture design is a direct result of the requests made by the Community, and it will improve a new spacial organization of the territory occupied by the quilombolas for over a century. It will also contemplate a requalification of their homes, a new Community Center, an administrative headquarters and a chapel to São Benedito, the praton saint of the Quilombo.